Hubungan antara Motivasi Berprestasi dan Dukungan Sosial Teman Sebaya dengan Resiliensi Akademik Peserta Didik SMK - Hilda Hanuf Hamida Zain; Elisabeth Christiana (Yayasan Literasi Sains Indonesia, 2026)
This study aims to determine the relationship between achievement motivation and peer social support with the academic resilience of grade XI students at SMK Negeri 2 Jombang. The research method used is a quantitative approach with a correlational design. The population in this study consisted of 380 students, with a sample of 80 students determined through purposive sampling. Data collection was conducted using a questionnaire in the form of a 5-point Likert scale. Data analysis was performed using multiple linear regression with the help of IBM SPSS Statistics 26. The results showed that achievement motivation had a positive and significant relationship with academic resilience (r = 0.614; p < 0.05). In addition, peer social support also showed a positive and significant relationship with academic resilience (r = 0.411; p < 0.05). Achievement motivation is a variable that has a stronger influence on academic resilience than peer social support. Simultaneously, achievement motivation and peer social support have a significant effect on academic resilience with an F value of 26.533 and an R square of 0.408, indicating that these two variables have a 40.8% influence on academic resilience. This study confirms that strengthening achievement motivation and peer social support play an important role in helping students cope with academic demands and challenges, especially in vocational high school environments.